Impact of Digital Learning Platforms on Behaviour Change Communication in Public Health Education - Udoudom, Uduak; George, Kufre; Igiri, Anthony (Pancasila International Journal of Applied Social Science, 2024)
This conceptual research explores the transformative potential of digital learning platforms in the realm of behaviour change communication within the context of public health education. With the rapid advancement of digital technology, the traditional methods of health communication are being reimagined, offering new opportunities and challenges for promoting healthier behaviours and lifestyles. The research seeks to understand the evolving landscape of digital learning platforms and their integration into public health education programs. It investigates how these platforms can be leveraged to design and disseminate behaviour change communication interventions effectively. The study examines the theoretical foundations that underpin behaviour change communication and the ways in which digital learning platforms can enhance these foundations. Furthermore, the research addresses the critical issue of accessibility and inclusivity, as digital platforms have the potential to bridge the gap between diverse populations in terms of health literacy, socio-economic status, and geographical location. By employing a conceptual framework that combines elements of health communication theory, pedagogy, and technology adoption models, this study aims to provide insights into the effective utilization of digital learning platforms for behaviour change communication. Findings indicate that the use of digital learning platforms has led to increase engagement in public health education. This exploration is expected to shed light on the potential of these platforms to drive positive health behaviour change among diverse populations and pave the way for more informed strategies in the field of public health education. Ultimately, this research aims to encourage further exploration and development of digital learning tools for behaviour change communication in public health, with the potential to make a significant impact on global health outcomes.